By demons possessed - Hodgell, P. C. (Patricia C.) (Hodgell, P. C. (Patricia C.) Kencyrath series., 2020)
"Something is preying on the gods of Tai-tastigon. Coerced into returning to the city the made her what she is, Jame Knorth--master thief, wily fighter and godling-in-the-making--finds citizen pitted against citizen. It seems many in the vast Lower Town have lost their shadows--no small matter when you realize that a shadow is cast by a soul. Some have gone mad while others wander like wraiths. Which means something is taking or destroying souls."--Provided by publisher.